2012
DOI: 10.1371/journal.ppat.1002797
|View full text |Cite
|
Sign up to set email alerts
|

Structural Mechanism of Trimeric HIV-1 Envelope Glycoprotein Activation

Abstract: HIV-1 infection begins with the binding of trimeric viral envelope glycoproteins (Env) to CD4 and a co-receptor on target T-cells. Understanding how these ligands influence the structure of Env is of fundamental interest for HIV vaccine development. Using cryo-electron microscopy, we describe the contrasting structural outcomes of trimeric Env binding to soluble CD4, to the broadly neutralizing, CD4-binding site antibodies VRC01, VRC03 and b12, or to the monoclonal antibody 17b, a co-receptor mimic. Binding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
241
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(261 citation statements)
references
References 60 publications
(119 reference statements)
19
241
1
Order By: Relevance
“…This correlation supports the relevance of the Env(-)ΔCT trimer structure to that of the functional virion Env spike. Our results provide a structural explanation for experimental observations suggesting that the ability to bind the Env trimer in its unliganded state represents a major factor in determining the neutralization potency of CD4BS antibodies (29,(46)(47)(48).…”
Section: B C a 90º 180ºsupporting
confidence: 54%
“…This correlation supports the relevance of the Env(-)ΔCT trimer structure to that of the functional virion Env spike. Our results provide a structural explanation for experimental observations suggesting that the ability to bind the Env trimer in its unliganded state represents a major factor in determining the neutralization potency of CD4BS antibodies (29,(46)(47)(48).…”
Section: B C a 90º 180ºsupporting
confidence: 54%
“…With the increasing understanding of the architecture of the viral spike (21,76,77), the possibility to generate stable soluble trimers that closely resemble the native spike (78,79), and the means to generate structurally arrested peptide mimetics of gp120 microdomains (31), a number of tools have become available which have promise to tailor future DARPin selections to specific domains of interest. As discussed above, based on our current data, this holds particular promise to improve envelope-specific DARPin identification and to harness the distinctive binding properties of DARPins for HIV inhibitor development.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of soluble CD4 (sCD4) produces little to no changes in the structures of gp120 cores (gp120 monomers with truncations in the N and C termini and variable V1V2 and V3 loops) (3), but results in rotation of the gp120 protomers within virion-bound Env trimers to create an open conformation distinct from the closed conformation of unliganded virion-bound trimers (4). Single-particle electron microscopy (EM) structures of recombinant native-like soluble Env gp140 trimers (SOSIPs) confirmed that they can adopt the same closed and open architectures as virion-bound Env trimers (5)(6)(7), thus the SOSIP substitutions (introduction of a disulfide bond linking gp120 to gp41 and an Ile→Pro mutation in gp41; ref. 6) do not appear to prevent transition to the open state.…”
mentioning
confidence: 99%
“…6) do not appear to prevent transition to the open state. Despite the plethora of recent crystal and EM structures at atomic and nearatomic resolutions of closed Env trimers, most in complex with broadly neutralizing antibodies (bNAbs) (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), only low-resolution structures derived from cryo-electron tomography of HIV-1 virions have been available for sCD4-bound open Env trimers (4)(5)(6)(7).…”
mentioning
confidence: 99%